ISSUES IN DEFINING REGIONAL DEVELOPMENT: EXPLORATION POTENTIAL FROM THE SEA OF AZORES - Paramio, Luz; Tiago, Teresa; Tiago, Flávio; Faria, Sandra (European Scientific Journal, ESJ, 2014)
Purpose – The purpose of this paper is to consider the methodological issues in last years of business development in the ocean-cluster research, which are holding back further development. Design/ methodology/ approach – The paper reviews several studies on business development and classifies definition inconsistencies found. Those differences are compared with methodological choices on sampling and with subsequent results. Research implications – Research on business development needs to introduce more attention to ocean-driven activities as a prerequisite for its advancement. The authors propose a framework based on the 10 issues identified to advance towards a consensus definition. Practical implications – Most measures launched are formulated based on studies done on inconsistent definitions and biased results. They might need to be reassessed. Findings – The diversity of definitions is explained by difficulties to obtain data and leads to different results. The authors propose a framework to advance towards a consensus definition, correctly contextualize the phenomenon of ocean-business investing and redefine public policies going forward. Originality/ value – The paper highlights the consequences of the lack of definition consistency in a research field of high interest for policy makers and practitioners.